Piano Quintet, Quartets, Trios etc. [de Wolfgang Amadeus Mozart] = Klavierquintett, Die Klavierquartette, -trios u.a. [von Wolfgang Amadeus Mozart] = Musique de chambre avec piano [de Wolfgang Amadeus Mozart] = Musica de camera con pianoforte [di Wolfgang Amadeus Mozart] - Mozart, Wolfgang Amadeus ((Complete Mozart Edition ;)
Contiene: KV 452, KV 498, KV 617, KV 356, KV 478, KV 493, KV 254, KV 496, KV 502, KV 542, KV 548, KV 564, KV 442.